RI 3334 Application Of Sand Filters To Oil-Field Brine-Disposal Systems ? Introduction (93e8faa1-0e91-4300-a0d1-51a7ae78e22d) - Sam S. Taylor (The National Institute for Occupational Safety and Health (NIOSH), 1937)
Disposal of brines produced with crude petroleum and natural gas is a continually increasing problem. The necessity for studying this problem has been realized more generally in recent years, and in August 1934 an agreement was made between the Kansas State Board of Health and the United States Bureau of Mines to conduct a cooperative technical study of methods of brine disposal. To date one paper in the technical press4/ and three reports5/6/ have been published in which are given results of studies carried on under this cooperative agreement. In the Mid-Continent fields, the methods used most generally for handling oil-field brines are: (1) Impounding in evaporation ponds; (2) controlled diversion into surface streams; and (3) injection into subsurface formations through wells assigned for this purpose. Various States recognize one or more of the methods as legally authorized procedure. Impounding brine in ponds and solar evaporation have proved inadequate as a general rule, owing, usually, to the porous nature of the soil, the low rate of evaporation, or both. Diversion, of